POTENSI PEMBAYARAN ZAKAT SECARA ONLINE DAN OFFLINE SERTA REALISASI DANA ZAKAT INDONESIA - Nilawati, Nilawati; Rijal, Khairul (I-Economics, 2019)
This study aims to describe the potential payment of zakat online and payment of zakat manually and the realization of zakat collection in Indonesia. Furthermore, this study seeks to highlight the effectiveness and efficiency between the potential of online zakat payments and manual zakat payments by muzakki and analysis of the realization of zakat receipts. This study uses a quantitative descriptive approach using secondary data from various literature. The results of this study indicate that digitalisation of zakat by examining the potential of online zakat payments is quite effective and efficient while for the total amount of zakat collection there is still dominance in the method of manual zakat payment and the realization of zakat revenue in Indonesia has always increased over the period 2012- 2017. However, there is a very large gap between the potential value and the amount of realization. During 2012-2017 the realization of zakat collection is still in the range of 0.2 - 1%. One factor is that the majority of Indonesians prefer to distribute their zakat directly to mustahik or through institutions that have not been officially under the auspices of the government such as mosques, mushollah, and other social institutions so that they cannot be recorded as a whole